2014
DOI: 10.1007/s00441-014-1977-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of somatostatin receptor types 3, 4 and 5 in the wild-type, SSTR1 and SSTR1/SSTR2 knockout mouse cochlea

Abstract: Somatostatin (SST) is a peptide hormone that exerts inhibitory effects mediated through binding to specific cell surface G protein-coupled receptors, of which five distinct subtypes (SSTR1-SSTR5) have been characterized. Our study performed on mouse cochlear hair cells shows the expression and localization of the three receptors (SSTR3-SSTR5) in wild-type (WT), single-knockout (SSTR1 KO) and double-knockout SSTR1/SSTR2 (DKO) mice. Similar SSTRs expression were observed in the inner hair cells (IHC), outer hair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…SST 5 is present in the rat retina, where its activation protects from AMPA–induced neurotoxicity ( Kiagiadaki et al, 2010 ). SST 5 is also present in cochlea, but its role and relevance are not yet known ( Radojevic and Bodmer, 2014 ). In the reproductive tract, SST 5 is present in Sertoli cells, where its expression is developmentally regulated ( Riaz et al, 2013 ).…”
Section: Somatostatin Receptormentioning
confidence: 99%
“…SST 5 is present in the rat retina, where its activation protects from AMPA–induced neurotoxicity ( Kiagiadaki et al, 2010 ). SST 5 is also present in cochlea, but its role and relevance are not yet known ( Radojevic and Bodmer, 2014 ). In the reproductive tract, SST 5 is present in Sertoli cells, where its expression is developmentally regulated ( Riaz et al, 2013 ).…”
Section: Somatostatin Receptormentioning
confidence: 99%
“…; Bodmer et al . ; Radojevic and Bodmer ) and demonstrated that Sstr1–5 are expressed in both the outer and inner HCs of the OC, and in a subset of supporting cells. We also demonstrated that somatostatin protects HCs from gentamicin‐induced HC death in vitro , and that octreotide protects HCs from gentamicin toxicity via the activation of Akt signaling (Brand et al .…”
mentioning
confidence: 97%
“…SST has been explored as a treatment for hormonal imbalance, diseases of disrupted cell proliferation, and dysregulated neuronal signaling (Harris 1990(Harris , 1994. We previously studied the somatostatinergic system in the mammalian inner ear (Radojevic et al 2011;Bodmer et al 2012;Radojevic and Bodmer 2014) and demonstrated that Sstr1-5 are expressed in both the outer and inner HCs of the OC, and in a subset of supporting cells. We also demonstrated that somatostatin protects HCs from gentamicin-induced HC death in vitro, and that octreotide protects HCs from gentamicin toxicity via the activation of Akt signaling (Brand et al 2014).…”
mentioning
confidence: 99%
“…To discover the potential functional mutations related to the growth traits in Hulun Buir sheep, we conducted exon sequencing of the SSTR1 gene, The ovine SSTR1 gene transcript has three exons and two introns (ENSOART00020017811.1) located on chromosome 18 (GenBank, Gene ID: 443202), encoding 1089 bp base (47398442–47400840) and 362 amino acid residues [ 33 ]. As a receptor of somatostatin, the SSTR1 gene plays an important role in many physiological processes, such as cell anti-proliferation, and inhibition of gastrointestinal motility and regulates a variety of signal transduction pathways [ 34 ]. Four SNPs (A345G, A285G, C309T and G951C) were all in Hardy–Weinberg equilibrium, which indicated an adequate population size of Hulun Buir sheep under random mating (or without selection) in the experiment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%